PELATIHAN MEMBUAT KARYA TULIS ILMIAH DENGAN MEMANFAATKAN ARTIFISIAL INTELIGENCE (AI) BAGI PELAJAR SMK BINUSA KOTA TANGERANG SELATAN - Tukiyat; Sajarwo Anggai; Arya Adhyaksa Waskita; Rafi Mahmud Zain; Muhammad Rafif Misbahuddin (Abdi Jurnal Publikasi, 2024)
Scientific writing is an essential skill that students, particularly those in Vocational High Schools (SMK), need to master. However, many students face challenges in understanding research methodology and technical skills, often resulting in scientific works that do not meet academic standards. This study aims to enhance students' scientific writing skills through training based on Artificial Intelligence (AI) technology. This Community Service Program (PKM) was conducted at SMK Binusa, South Tangerang City, involving 22 participants from the Computer Network Engineering department. The implementation method consisted of theory sessions, practical sessions, and workshop discussions. Evaluation was carried out using pre-tests and post-tests to measure participants' understanding improvements. The training results revealed that most participants showed enhanced scientific writing abilities, with 43% rated as excellent and 31% as good. Additionally, the training materials and instructor quality were positively evaluated, with 57% of participants rating the materials as excellent and 60% rating the instructors as excellent. This training provided significant benefits, particularly in fostering innovation and participants' digital literacy skills. Nevertheless, several areas for improvement were identified, such as delivering more interactive materials and diversifying training methods. This program recommends integrating interactive technology and continuous training to support the development of scientific writing skills for vocational students, thereby enhancing their competitiveness in the future.